(3QjGV GdBOGH hfRgI GdCMHGHs - (3eLghds
(3ChdgG (B:s
(3hHYO abO TQYJ ai LeY LRA dWja eMJh ef CfhGY GdOH Ydi cd eYfi XQja ? MSf GdebGUO hGdfXGe , YPGH GdCdaGX hGdCfSLGe s
(3BNQgG (B:s
(3efbhd ef eUfa CHj GdaJM GdeSei cTa GdHjGf Yf UaGJ GdMjhGf hgPG BNQ eG dNU ef JCdja GdTjN CHj GdaJM s
(3JHUQI GdYfhGf (B:s
(3GNJUGQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B56 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs